The last house guest : a novel / [large type] - Miranda, Megan (Wheeler Publishing, a part of Gale, a Cengage Company, 2019)
A suspenseful novel about an idyllic town in Maine dealing with the suspicious death of one of their own -- and her best "summer" friend, who is trying to uncover the truth... before fingers point her way. Littleport, Maine, has always felt like two separate towns: an ideal vacation enclave for the wealthy, whose summer homes line the coastline; and a simple harbor community for the year-round residents whose livelihoods rely on service to the visitors. Typically, fierce friendships never develop between a local and a summer girl -- but that's just what happens with visitor Sadie Loman and Littleport resident Avery Greer. Each summer for almost a decade, the girls are inseparable -- until Sadie is found dead. While the police rule the death a suicide, Avery can't help but feel there are those in the community, including a local detective and Sadie's brother, Parker, who blame her. Someone knows more than they're saying, and Avery is intent on clearing her name, before the facts get twisted against her.